Pengaruh Kualitas Pelayanan terhadap Loyalitas dengan Mediasi Kepuasan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Customer loyalty is a very important factor for companies to be able to continue to carry out production activities from their business. Making loyal customers with the Company will help in increasing business competitiveness. This research was conducted in order to test the effect of service quality on loyalty by using satisfaction mediation at the Honda Jayakarta Denpasar Car Repair Shop. The population is 65 customers and all of them are used as samples. Analysis of research data will use the method of path analysis or path analysis. The findings from the tests conducted are that there is a mediating role of satisfaction in increasing the effect of service quality on loyalty. It is recommended for the company to always improve the quality of service to customers so that they become satisfied and loyal to the company